Merkel cell carcinoma of the gluteal region: a rare case report and literature review - Mahmut Corapli; Burcin Pehlivanoglu; Haci Taner Bulut; Huseyin Alakus; Nadiye Akdeniz (Journal of the Pakistan Medical Association, 2021)
Merkel cell carcinoma (MCC) is a rare cutaneous neuroendocrine cancer that shows aggressive biologic behavior. Although it usually occurs in sun-exposed areas, it can rarely be seen in non-sun-exposed sites. Here, we present a 66-year-old woman with MCC arising from the right gluteal region that was treated wide excision and adjuvant chemoradiotherapy. In the 24th month follow-up, the case was disease and recurrence free, representing the longest survival among patients with gluteal MCC. Early diagnosis and treatment are important to improve survival rates in patients with non-sun-exposed MCC. Keywords: Merkel cell carcinoma, non-sun-exposed, Continuous...